Pengembangan Media Pembelajaran Bima Pandawa Untuk Peningkatan Pemahaman Konsep Wayang - Astriyanto, Febri Kalingga; Purwati, Purwati; Istiningsih, Galih (Universitas Muhammadiyah Magelang, 2020)
The purpose of this study was to determine (1) the characteristics, (2) validity and (3) the effectiveness of BIMA PANDAWA learning media. The study was conducted in grade IV SDN Sriwedari 1 & 2. This research is a type of research and development research. The research design used is a modification of the Borg and Gall steps. The results of this study indicate that the learning media of BIMA PANDAWA is valid, feasible and effectively used. This is evidenced from the validity results assessed by expert validation for instructional media from the material aspect 90% (very valid), validation for media from the design aspect scores 87.2% (very valid) and validation of learning support devices get an average score 90% (very valid). Anova posttest test analysis results in the experimental and control classes have sig. 0.002 <0.05 so there is a significant difference. The results of this study are expected to be a reference or input for the development of education and increase the study of science, especially in learning Puppet Pandhawa.